Patriotic sociability and defence of the constitutional cause - Araújo, Ana Cristina (2021)
The philosophical modernity of the Enlightenment contributed to change cultural agents and international knowledge networks. The European agents and values of eighteenth-century intellectual communication were expanded and secularized. New forms of intellectual and patriotic sociability emerged in the public sphere. In this context, sociability was marked by the establishment of philanthropic, economic and patriotic associations. This study highlights the importance of three associations created and imagined in the late 18th and early 19th centuries: the Sociedade dos Mancebos Patriotas of Coimbra (1780); the Montepio Literário (1813); and the Sociedade Patriótica Literária de Lisboa (1822).